Integração das tecnologias digitais na prática pedagógica: Proposta de um E-book com recursos digitais para os docentes do Instituto Federal do Maranhão - IFMA - MENDES, Shirlene Coelho Smith (2021)
This study deals with the integration of digital technologies in pedagogical practice: proposal for an E-book of digital tools for teachers at the Federal Institute of Maranhão, Campus Centro Histórico. The general objective was to investigate the pedagogical practice from the perspective of mobile digital technologies, the integration that digital tools promote at the Federal Institute of Maranhão - Campus Centro Histórico. The problem was outlined based on the following question: What knowledge about mobile digital technologies is demonstrated by the teachers of the Federal Institute of Maranhão - Campus Centro Histórico and how are they being integrated in the pedagogical practice? Thus, we used as bibliographic references: Bacich (2017), Bottentuit Junior, Menez e Wunsch (2018), Behar (2013), Camargo e Daros (2018), Carvalho (2018), Candau (1983), Castells (1999), Coutinho (2011), Gauthier e Tardif (2014), Horn e Staker (2015), Imbernón (2012), Kenski (2013), Kapp (2012), Levy (2010), Libâneo (2006), Modelski (2015), Moran, Masetto e Behrens (2015), Perrenoud (2000), Prensky (2020), Oliveira e Pochamann (2020), Schön (1992), Valente (2018), among others. The methodology used was the case study, with a qualitative approach, of an exploratory and descriptive nature. The data collection instruments used were texts, documents, online questionnaires carried out by the Google digital forms platform and observation carried out at the research site. For the analysis and interpretation of the data, we used graphs for the quantitative questions and an answer table for the qualitative questions. The final product of the research was described in the seventh section, where it addresses the conception and elaboration of the E-book of digital tools for teachers, which was elaborated from precepts of digital culture with the objective of integrating digital technology in the pedagogical practice of the teachers of the Federal Institute of Maranhão - Campus Centro Histórico. The results obtained in the research indicate that the enrichment of the pedagogical practice through a methodological approach with the integrated use of digital technologies it is something necessary in the researched institution. They also reveal that the teaching staff, despite having a good professional qualification, lacks continuing education at the level of improvement, extension, continuing education, etc., in digital technologies for teaching. The study also pointed out that although the digital culture allows countless possibilities for the teaching-learning process, the teacher needs to be well trained, well oriented, which can be considered as a way to acquire 18 digital skills, it also showed that the culture of teacher training is fragmented and sometimes decontextualized from reality, which reveals a weakened formation in the face of the emergencies of the new student profile.